2018
DOI: 10.3389/fped.2018.00130
|View full text |Cite
|
Sign up to set email alerts
|

A Novel de Novo Mutation in the CD40 Ligand Gene in a Patient With a Mild X-Linked Hyper-IgM Phenotype Initially Diagnosed as CVID: New Aspects of Old Diseases

Abstract: Mutations in the CD40 ligand (CD40L) gene (CD40LG) lead to X-linked hyper-IgM syndrome (X-HIGM), which is a primary immunodeficiency (PID) characterized by decreased serum levels of IgG and IgA and normal or elevated IgM levels. Although most X-HIGM patients become symptomatic during the first or second year of life, during which they exhibit recurrent infections, some patients exhibit mild phenotypes, which are usually associated with hypomorphic mutations that do not abrogate protein expression or function. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…This case illustrates and supports the growing potential for exome or whole genome sequencing in accurate PID diagnostics. We speculate that HIGM may be under-or misdiagnosed, and clinically milder phenotypes in particular could be misdiagnosed as other immunodeficiencies such as CVID, as occurred with our patient and has been reported previously (15). Genetic investigation is becoming increasingly available and utilized, thus potentially enabling better understanding of genotypes and phenotypes, and consequently improved care and genetic counseling for patients and family members.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…This case illustrates and supports the growing potential for exome or whole genome sequencing in accurate PID diagnostics. We speculate that HIGM may be under-or misdiagnosed, and clinically milder phenotypes in particular could be misdiagnosed as other immunodeficiencies such as CVID, as occurred with our patient and has been reported previously (15). Genetic investigation is becoming increasingly available and utilized, thus potentially enabling better understanding of genotypes and phenotypes, and consequently improved care and genetic counseling for patients and family members.…”
Section: Resultssupporting
confidence: 62%
“…HIGM variants typically affect the extracellular domain, thus resulting in inability of CD40-CD40L binding. Variants in exon 1 decrease the expression of CD40L (15). In this case, we found a nonsense variant in exon 1, and the pathogenicity was illustrated by impaired upregulation of CD40L on activated CD4 cells, as assessed by flowcytometry (Figure 3).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The balance of immunoglobulins, IgM, IgG, and IgA are involved in cryptococcal immune response. X-linked hyper-IgM immunodeficiency syndrome is caused by mutations that occur in the CD40 ligand gene which results in decreased levels of IgG and IgA and elevated IgM has been shown to increase susceptibility to infections including invasive and cutaneous cryptococcosis particularly observed in pediatric male patients [ 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 ]. In addition, in vitro assays using C. neoformans found that IgM but not IgG inhibited Titan cell formation, reduced capsule thickness, and decreased the expression of chitin synthetase genes ( CHS1 , CHS2 , CHS8 , α-1–3-glucan synthetase ( AGS1 ), and β-1,3-glucan synthetase ( FKS1 ) [ 156 ].…”
Section: Associations Between Human Attributes and Cryptococcosismentioning
confidence: 99%
“…[20] CD40LG acts as an immune modulator in activated T cells [21] Inactivation of CD40LG gene resulted from the insertion of an AluYb8 element in exon 1 responsible for a total deficiency of CD40 ligand expression by T lymphocytes [22] Interestingly, some study shows that, not all mutations occur in CD40LG gene may cause XHIGM [23] Different mutations have been reported. [23][24][25][26][27][28][29][30][31][32] As far as we know there are two options for treatment, either hematopoietic stem cell transplantation or intravenous immunoglobulin replacement therapy. [33] but it is sometimes completely ignored because of low recognition and limited knowledge of this rare disease.…”
Section: Introductionmentioning
confidence: 99%